Understanding variation in length of hospital stay for COPD exacerbation: European COPD audit. Issue 1 (5th March 2016) - Ruparel, Mamta; López-Campos, Jose Luis; Castro-Acosta, Ady; Hartl, Sylvia; Pozo-Rodriguez, Francisco; Roberts, C. Michael
Chronic obstructive pulmonary disease (COPD) care across Europe has high heterogeneity with respect to cost and the services available. Variations in length of stay (LOS) may be attributed to patient characteristics, resource and organisational characteristics, and/or the so-called hospital cluster effect. The European COPD Audit in 13 countries included data from 16 018 hospitalised patients. The recorded variables included information on patient and disease characteristics, and resources available. Variables associated with LOS were evaluated by a multivariate, multilevel analysis. Mean±sd LOS was 8.7±8.3 days (median 7 days, interquartile range 4–11 days). Crude variability between countries was reduced after accounting for clinical factors and the clustering effect. The main factors associated with LOS being longer than the median were related to disease or exacerbation severity, including GOLD class IV (OR 1.77) and use of mechanical ventilation (OR 2.15). Few individual resource variables were associated with LOS after accounting for the hospital cluster effect. This study emphasises the importance of the patients' clinical severity at presentation in predicting LOS. Identifying patients at risk of a long hospital stay at admission and providing targeted interventions offers the potential to reduce LOS for these individuals. The complex interactions between factors and systems were more important that any single resource or organisational factor in determining differences in LOS between hospitals or countries. LOS determined by COPD exacerbation severity and interactions within hospitals constituting effective patient care http://ow.ly/XD9hy